PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KEPALA BERNOMOR TERSTRUKTUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 28 PADANG TAHUN PELAJARAN 2013/2014 - Dian Putri, Rafni; Zulfaneti, Zulfaneti; sovia, Anny (STKIP PGRI Sumbar, 2014)
ABSTRACT This research was designed for determining whether the mathematics conceptual understanding of students class VIII.5 taught by using technique Numbered Head of Structured cooperative learning was better than that of students class VIII.6 taught by using conventional learning. This was an experimental research wich used pre eksperimental design: static group comparison. The population in this research is the students in class VIII SMPN 28 Padang except class VIII.1 because it is superior class. The sampling was done by purposive sampling. The data was collected by using a on posttest mathematics conceptual understanding. The results of hypothesis test showed that P-value=0,036 was smaller than α=0,05, indicating that the hypothesis was accepted. Thus, it was concluded that the mathematics conceptual understanding of students class VIII.5 taught by using technique Numbered Head of Structured cooperative learning was better than that of students class VIII.6 taught by using conventional learning of SMPN 28 Padang.